Remineralizing potential of various agents on dental erosion - Rani Somani; Shipra Jaidka; Deepti Jawa Singh; Vanika Arora (Elsevier, 2014)
Aim: The purpose of this study is to compare the effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP, Tooth Mousse) containing and casein phosphopeptide-amorphous calcium phosphate with fluoride (CPP-ACPF, Tooth Mousse Plus) containing pastes on dental erosion. Materials and methods: Thirty permanent non-carious premolars indicated for orthodontic extraction were included in this study and were sectioned in mesiodistal direction vertically. After immersion in the carbonated drink for 14 min, samples were treated with various remineralizing pastes which were CPP-ACP containing paste (Tooth Mousse) and CPP-ACPF containing paste (Tooth Mousse Plus) according to the manufacturer's instructions. Vickers Microhardness was recorded at baseline, after exposure to erosive drink and after treatment with remineralizing pastes. Data obtained was statistically analysed using Student t-test with a level of significance set at p < 0.05. Results: CPP-ACP (Tooth Mousse) and CPP-ACP with fluoride (Tooth Mousse Plus) resulted in 30.52% and 38.98% increase in post-erosion microhardness values respectively. The remineralizing potential of CPP-ACP with fluoride containing paste (Tooth Mousse Plus) was significantly better than that of CPP-ACP containing paste (Tooth Mousse) (p < 0.05). Conclusion: Casein phosphopeptide-amorphous calcium phosphate with fluoride (CPP-ACPF, Tooth Mousse Plus) can be recommended to be used in preventing erosive tooth wear from acidic beverages.